Oil palm-cattle integration: Farmer perception of Ganoderma infection - Suteky Tatiek; Dwatmadji Dwatmadji; Bustaman Hendri (BIO Web of Conferences)
Oil Palm- cattle integration is part of the government initiatives to supply the huge demand for beef in Indonesia. It also maximizes land usage to raise farmer productivity and profitability. The issue of cattle in oil palm could spread Ganoderma disease influencing the deployment of oil palm-cattle integration. The purpose of this study is to assess farmers’ perception of cases of Ganoderma infection in oil palm plantations. The research was conducted in 6 districts of Bengkulu province (Bengkulu City, Seluma, Central Bengkulu, North Bengkulu, Muko-muko, and Kaur). The study’s target group included male and female heads of rural agricultural households either practicing integrated oil palm-cattle systems (IOPCS) or not practicing IOPCS. In-person interviews were conducted with all respondents using a standardized questionnaire to collect data. The findings indicated that although farmers perceive several potential benefits from integrating cattle into oil palm plantations, they also confront challenges concerning security, finance, knowledge, feed availability, and disease in the cattle. In addition, many farmers were failing to recognize that their farms were contaminated with Ganoderma. Only a few respondents thought there was a link between Ganoderma infection and cattle integrated in oil palm. In this study, we will also discuss the relationship between farmer education level and their knowledge about Ganoderma infection and also compare the incidence of Ganoderma infection in IOPCS and non-IOPCS based on farmer perception.